Third Sector Organizational Challenges in Provision of Clean Water Services in Darungan Village, Jember Regency - Mohammad Baladdudin Dayar; Edi Wahyudi; Supranoto Supranoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted to find out how the involvement of the third sector in the public service of providing clean water in Darungan Village, Tanggul District, Jember Regency. Darungan Village from 1970 to 1980 is a portrait of the government's failure to fulfill the needs of the public sector for clean water. This failure can be seen from the absence of the government in an effort to fulfill public needs in this sector. This is because the geographical location of Darungan Village is isolated and the level of education of the majority of the community is quite low. By referring to the idea of Bransend's co-production theory, that to involve the community actively in public services to revive the democratization of society which is considered to be starting to degrade, it allows the third sector or also known as the community to be involved in public services, especially in the sector of meeting water needs. clean in Darungan Village. Clean water services carried out by the third sector in Darungan Village are carried out by an organization named HIPPAM (Himpunan Penduduk Pemakai Air Minum) which has been established in 2000 to date, in collaboration with the PU Cipta Karya Office, Jember Regency. The government provides assistance in the form of clean water facilities which will be managed independently by the community. The results of this study are the challenges faced by third sector organizations in providing clean water in Darungan Village.